(untitled) (Elmergib Journal of Human Sciences, 2026)
This research examines the role of context in determining linguistic meaning, focusing on the Qur’anic text. It presents the concept of context among classical and modern Arab linguists, demonstrating how they analyzed context and clues to ascertain the intended meaning of shared terms. The research also clarifies the semantic functions of context in interpreting the Qur’anic text, drawing on examples from the Holy Qur’an. It highlights the intellectual connections between the Arabic linguistic heritage and modern linguistics, acknowledging the scholarly contributions of the Arabic linguistic heritage. The study affirms that context represents a central mechanism for producing meaning and regulating linguistic interpretation.